Development of the myzozoan aquatic parasite Perkinsus marinus as a versatile experimental genetic model organism - Einarsson, Elin; Lassadi, Imen; Zielinski, Jana; Guan, Qingtian; Wyler, Tobias; Pain, Arnab; Gornik, Sebastian G.; Waller, Ross F. (Protist, 2021)
The phylum Perkinsozoa is an aquatic parasite lineage that has devastating effects on commercial and natural mollusc populations, and also comprises parasites of algae, fish and amphibians. They are related to dinoflagellates and apicomplexans and thus offer excellent genetic models for both parasitological and evolutionary studies. Genetic transformation was previously achieved for Perkinsus spp. but with few tools for transgene expression and limited selection efficacy. We sought to expand the power of experimental genetic tools for Perkinsus using P. marinus as a model. We constructed a modular plasmid assembly system for expression of multiple genes simultaneously. We developed efficient selection systems for three drugs, puromycin, bleomycin and blasticidin, that are effective in as little as three weeks. We developed eleven new promoters of variable expression strength. Furthermore, we identified that genomic integration of transgenes is predominantly via non-homologous recombination but with transgene fragmentation including deletion of some elements. To counter these dynamic processes, we show that bi-cistronic transcripts using the viral 2A peptides can couple selection to the maintenance of the expression of a transgene of interest. Collectively, these new tools and insights provide great new capacity to genetically modify and study Perkinsus as an aquatic parasite and evolutionary model.
Gesehen am 05.11.2021